I sure don't see anything obvious, but
(2sinx cosx/cosx)^2 = 4sin^2x
(2sin(2x)cos(2x)/cos(2x))^2 = 4sin^2(2x) = 16sin^2x cos^2x
sin^2(x)/(cos^2(2x)-sin^2(2x))^2 = sin^2x/(sin^4x+cos^4x-6sin^2x cos^2x)
adding those up, you get
4sin^2x + 16sin^2x cos^2x + sin^2x/cos^2(4x)
= sin^2(x)/cos^2(4x) (4cos(2x)+12cos(4x)+4cos(6x)+1)
there are so many ways to massage this kind of stuff, you can stop almost anywhere and say that's it, unless you have some specific target in mind.
Find value of
(sin^2(2x)/cos^2(x)) + (sin^2(4x)/cos^2(2x)) + (sin^2(x)/cos^2(4x))
1 answer